Matrix converter for frequency changing power supply applications - Lopez Arevalo, Saul (2008)
The purpose of this work is to investigate the design and implementation of a 7.5kVA Matrix Converter-based power supply for aircraft applications (GPU Ground Power Unit). A Matlab/Simulink as well as SABER simulation analysis of the candidate Matrix Converter system is provided. The design and implementation of the Matrix Converter is described, with particular attention to the strict requirements of the given power supply application. This AC-AC system is proposed as an effective replacement for the conventional AC-DC-AC system which employs a two-step power conversion.